"El Silencio": Conceptualizations of Latina Immigrant Survivors of Intimate Partner Violence in the Midwest of the United States. (April 2016) - Silva-Martínez, Elithet
This critical ethnography explored the experiences of battered, immigrant, Spanish-speaking Latinas in the Midwest of the United States. It relied on Chicana and Mujerista frameworks for understanding help-seeking. Although there has been progress in documenting intimate partner violence in the United States, there is less knowledge concerning this issue with undocumented Latinas. The methodology implemented two stages: (a) observations and informal interviews and (b) formal interviews. The findings reveal multiple sides of "el silencio." Maintaining the silence, or breaking it, is surrounded by exchanges with the internal voice parallel to personal experiences with violence at different points in life. It is also affected by cultural expectations in home and host country.